In hospital outcomes of orbital/rotational coronary atherectomy in diabetic vs non-diabetic population: insights from the nationwide inpatient sample. (14th October 2021) - Kurpad, K; Mehta, H; Sohal, S; Garg, N; Gopal, S; Zainib, M; Suthar, K; Jumkhawala, S; Ahsan, M; Hawthorne, K
Abstract: Background: Atherectomy (AT) using an orbital/rotational system is useful in altering calcified plaque thereby facilitating stent placement and optimal stent expansion. Patients with diabetes mellitus (DM) are known to have a higher rate of complications after percutaneous coronary intervention. We aimed to assess the incidence of major adverse cardiovascular events after atherectomy in the diabetic population using a nationwide inpatient sample (NIS). Methods: NIS-HCUP database from 2015–2017 was used to identify patients who underwent atherectomy. A cohort of patients with and without diabetes was identified. Demographics, in-hospital outcomes, complications in both groups were compared. Statistical significance was assigned at p<0.05. Results: Out of 6184 patients who underwent AT, 3134 (50.6%) patients had DM. Baseline characteristics have been outlined in the table below. Complications were comparable between the two groups except for higher incidence of post-procedure VTE in Diabetic patients. In-hospital mortality was lower among patients with DM (2.24% vs 3.29%, p-0.27), while the mean length of stay (5.92 vs 4.91 days, p-0.002) and the hospitalization charges (165118.4 vs 151226, p-0.04) were higher, but this difference in length of stay and hospitalization charges were nullified on multivariate regression. Conclusion: Our study suggests that an AT for severely calcified plaque in the coronary artery is a safe option in patients with DM with comparable in-hospital complications and outcomes to non-DM patients. Funding Acknowledgement: Type of funding sources: None.